Market concentration and the Danish rental market - Denis Gorea; Thomas Krause; Per Andersen (Danmarks Nationalbank, 2022)
This memo analyzes the evolution of firm ownership concentration in the private Danish rental market and its link to rental prices. We show that the overall increase in rental market concentration between 2010 and 2020 is mainly driven by the rental market in the Capital Region. Further, we document a positive empirical link between market concentration and rental prices.
Keywords: 330; Business enterprises and households; Price development; Housing finance